2013
DOI: 10.4037/ajcc2013722
|View full text |Cite
|
Sign up to set email alerts
|

CNE Article: Safety Culture In Australian Intensive Care Units: Establishing A Baseline For Quality Improvement

Abstract: A closed-book, multiple-choice examination following this article tests your under standing of the following objectives:1. Identify the importance of and interest in safety culture in the health care system. 2. Describe how workplace safety culture contributes to patient outcomes. 3. Define strategies that may improve safety and patient outcomes. Background Workplace safety culture is a crucial ingredient in patients' outcomes and is increasingly being explored as a guide for quality improvement efforts. Objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
57
1
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 38 publications
13
57
1
8
Order By: Relevance
“…Similarly to other studies (20)(21) medical professionals scored higher on Teamwork climate than nursing professionals. It is not unusual for operational professionals to hold different perceptions than leadership regarding safety issues (22) .…”
Section: Safety Climate Stress Recognition Perception Of Managementmentioning
confidence: 73%
See 1 more Smart Citation
“…Similarly to other studies (20)(21) medical professionals scored higher on Teamwork climate than nursing professionals. It is not unusual for operational professionals to hold different perceptions than leadership regarding safety issues (22) .…”
Section: Safety Climate Stress Recognition Perception Of Managementmentioning
confidence: 73%
“…Of the ten ICUs analyzed in a study conducted in Australia and New Zealand, nine also presented weak scores in Perception of management; the highest score was in Teamwork climate, demonstrating that respondents were more positive with regards to teamwork collaboration than the other domains (20) . Similarly to other studies (20)(21) medical professionals scored higher on Teamwork climate than nursing professionals.…”
Section: Safety Climate Stress Recognition Perception Of Managementmentioning
confidence: 99%
“…63 Establishing a workplace safety culture is now considered a basic requirement for the implementation of quality improvement programs. Chaboyer and colleagues 64 conducted the first multisite study that examined perceptions of safety culture within 10 Australian ICUs, and they reported that fewer than half of respondents identified the safety culture as positive. Differences between the different professional groups in the ICU nurture the suggestion that improvement programs should be tailored to the stakeholders' respective characteristics.…”
Section: Safety Issuesmentioning
confidence: 99%
“…Differences between the different professional groups in the ICU nurture the suggestion that improvement programs should be tailored to the stakeholders' respective characteristics. 64 Adequate risk assessment tools may help nurses considerably in enhancing patient safety. Prentiss 65 clearly described the development and subsequent validity and reliability testing of such an instrument for the early recognition of pediatric venous thromboembolism.…”
Section: Safety Issuesmentioning
confidence: 99%
“…W Chaboyer ir kt. Australijoje atliktas požiū-rio į saugą tyrimas nustatė, kad komandinio darbo aplinka įvertinta aukščiausiais balais, o vadovybės požiūris į saugą -žemiausiais balais [5]. Mūsų atlikto tyrimo rezultatai parodė, kad sveikatos priežiūros specialistai yra patenkinti savo darbu, komandinio darbo aplinka, tačiau žemiausiais balais įvertinta vadovybės požiūrio į saugą dimensija atskleidžia, kad vadovybė nepakankamai kreipia dėmesio į pacientų saugą.…”
Section: Tyrimo Rezultatų Aptarimasunclassified